Transforming Education Outcomes in Africa Learning from Togo - Hoogeveen, Johannes; Rossi, Mariacristina (Springer Nature, 2019)
Good education changes lives. It is therefore unsurprising that improved schooling plays a central part in most development strategies. At the same time, the expansion of school attainment alone is not sufficient to guarantee improved welfare. This open access book focuses on one country in West Africa, Togo, to explore what a country that has successfully increased enrollment rates can do to enhance learning outcomes. The authors explore different avenues for improvement, including enhancing the efficiency with which resources are used; increasing the qualifications of teachers; and through greater community involvement in school management. There is scope for improvement along all these dimensions, yet changes at the margin are insufficient to bring about the transformation needed to bring about acceptable levels of learning. Important reading for anyone interested in understanding the pathways to improving the education system in Togo and other developing countries. Except where otherwise noted, this book is licensed under a Creative Commons Attribution 3.0 IGO License. To view a copy of this license, visit http://creativecommons.org/licenses/by/3.0/igo/.